The Relationship of the Social Identity with the Quality of Parents –Child relationship among the Girl Students of Secondary High School: Comparative study of the Role of Fathers and Mothers - somayeh kazemeyan; maryam karimi (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2018)
Parent-child relationships affect the various aspects of adolescent development and social identity is one of the dimensions of identity that affects the life of the individual and society. The purpose of this study was to investigate the relationship between social identity and the quality of parent-child relationships among the girl students of secondary high school and to determine the difference between mother-child and father-child relationships as an important predictor of social identity. For this purpose a sample of 319 adolescent girls from the secondary high school in Yazd were selected randomly in a multi-stage cluster sampling method to participate in research. The instruments used in the research included parent-child relationship questionnaire (PCRS) and Social Identity Questionnaire. For data analysis, Pearson correlation and regression analysis were used. The results of the study showed that there is a positive and significant relationship between the quality of relationship with the father and the social identity of the girl adolescents (r = 0.26, P = 0.001) and the quality of their relationship with the mother(r= 0.18, P = 0.01). Regression results showed that just the quality of relationship with father (P = 0.001) could significantly predict the social identity of adolescent girls. As a result, the relationship with the father contributes more to predict the social identity of the girls.